Computed tomography-based investigation of degenerative neural cervicothoracic foraminal stenosis as a potential mechanism for Horner syndrome - Ong, Joshua; Kurokawa, Mariko; Khanna, Sangeeta; De Lott, Lindsey B.; Kurokawa, Ryo; Sharma, Aseem (Frontiers in Ophthalmology, 2025)
PurposeTo investigate the presence and/or severity of cervicothoracic foraminal stenosis between the C7 and T3 segments could account for Horner syndrome, otherwise deemed to be idiopathic in nature.MethodsThis study was an IRB-approved, retrospective study that included 28 patients [mean ± standard deviation (age: 54.5 ± 18.7 years)] with a confirmed diagnosis of Horner syndrome, absence of any identifiable cause, and availability of a neck CT/CT angiogram obtained within 6 months of the diagnosis. A neuroradiologist masked to the laterality of Horner syndrome reviewed the CT scans, documenting the presence/severity of foraminal stenosis at levels C7-T1, T1-2, and T2-3 on a 4-point Likert scale defined as follows: 0, none; 1, mild; 2, moderate; and 3, severe narrowing, with grades 1, 2, and 3 signifying <1/3rd, 1/3rd–2/3rd, and >2/3rd stenosis of the expected normal foraminal dimension.ResultsForaminal stenosis was present ipsilateral to the side of Horner syndrome in four (14.3%) patients and on the contralateral side in five (17.8%) patients. No significant difference in the extent of ipsilateral and contralateral foraminal stenosis was present at C7-T1 (p = 0.66), T1-2 (p = 0.32), or T2-3 (p = 0.75) levels. Mean ipsilateral (0.33 ± 1.0) and contralateral (0.33 ± 1.1) cumulative foraminal stenosis ddddscores were not significantly different (p = 1). Mean maximum foraminal stenosis scores ipsilateral (0.22 ± 0.59) and contralateral (0.30 ± 0.81) to the side of Horner syndrome were also comparable (p = 0.54).ConclusionWith the low prevalence of foraminal stenosis at C7-T3 segments and the equivalent prevalence and severity of foraminal stenosis ipsilateral and contralateral to the side of Horner syndrome, foraminal stenosis is unlikely to be a common causative mechanism for Horner syndrome.